"Peer-led support for long term health conditions : its functions, benefits and challenges and how the role of a facilitator could increase effectiveness" : a Masters thesis - Hughes, Emily (Massey University, 2017)
Peer-led support groups for long-term health conditions are inexpensive and beneficial resources. However, literature on peer-led support is minimal and suggests that these groups face many challenges. The current study endeavored to explore the challenges and functions of peer-led support groups for long-term health conditions; further, examining how the implementation of the role of a Facilitator for these groups could negate some of the challenges and increase the prevalence and effectiveness of groups. Through focus groups and individual interviews with Group Leaders, Health Professionals and Group Participants involved in peer-led support groups, the current study identified 7 emergent themes. These themes were discussed and analyzed, particularly in relation to the experience of peer-led support groups and the possibility for the development of the role of a facilitator in the future.
Keywords: Chronically ill; Services for; Self-help groups; Group facilitation; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Social work::Disability research